2011
DOI: 10.1371/journal.pone.0025667
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylated NSSR1 Is Induced by Androgen in Mouse Epididymis and Phosphorylated NSSR1 Is Increased during Sperm Maturation

Abstract: NSSR1 (Neural salient serine/arginine rich protein 1, alternatively SRp38) is a newly identified RNA splicing factor and predominantly expressed in neural tissues. Here, by Western blot analysis and immunofluorescent staining, we showed that the expression of dephosphorylated NSSR1 increased significantly during development of the caput epididymis. In adult mice, phosphorylated NSSR1 was mainly expressed in the apical side of epithelial cells, and dephosphorylated NSSR1 in caput epididymis was upregulated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…This cytosolic localization persists in testicular cancer, and is also seen in liver, endometrial and urothelial cancers (Uhlen et al 2015). Dephosphorylation of SRSF10 is induced by androgen in mouse epididymis and phosphorylated SRSF10 expression is increased during sperm maturation (Xiao et al 2011). 9.…”
Section: Heart Developmentmentioning
confidence: 97%
“…This cytosolic localization persists in testicular cancer, and is also seen in liver, endometrial and urothelial cancers (Uhlen et al 2015). Dephosphorylation of SRSF10 is induced by androgen in mouse epididymis and phosphorylated SRSF10 expression is increased during sperm maturation (Xiao et al 2011). 9.…”
Section: Heart Developmentmentioning
confidence: 97%
“…At 1 or 12 hr after vector injection or 4-6 hr after nocodazole injection (16-18 hr after viral injection), animals received an overdose of pentobarbital (100 mg/kg intraperitoneally) and were perfused transcardially with ice-cold 100 mM sodium PBS (pH 7.4), followed by 4% PFA in phosphate buffer (PB) (pH 7.4). After tissues were postfixed for 24 hr at 4°C in PFA, 34 10-20 lm coronal sections were cut using a cyrosection microtome and then the slides were directly sealed with mounting medium (Prolong Antifade Gold with DAPI [4¢,6¢-diamidino-2-phenylindole]; Molecular Probes).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Heat shockinduced NSSR1 dephosphorylation was found to display splicing thermotolerance mediated by the Hsp27 protein (Shi et al, 2011). Recently, we found that NSSR1 is expressed in mouse reproductive tissues such as the uterus and epididymis and, more interestingly, that the level of de-phosphorylated NSSR1 proteins in the mouse caput is upregulated during the first 3 weeks after birth, and was induced by androgen in the mouse epididymis Xiao et al, 2011), indicating the potential roles that dephosphorylated NSSR1 protein might play during development of the epididymis and sperm maturation. It therefore appears that dephosphorylated NSSR1 proteins are involved in multiple aspects of physiological functions in different tissues and cells, including splicing, and that more functions need to be assigned to dephosphorylated NSSR1.…”
Section: Introductionmentioning
confidence: 96%